ANALISIS KELAYAKAN SISTEM TANAM CABAI MERAH DAN BAWANG MERAH PADA MUSIM HUJAN DAN KEMARAU - Geubrina Maghfirah; Dadang Dadang; Eka Kumala Intan Putri; Yeni Yanti; Chairul Amni; Irda Yunita (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2024)
This research aims to reduce the impact of losses on red chili and shallot production during the rainy and dry seasons in Tegal Regency. The survey method was conducted involving 140 respondents from red chili farmers. The data was then analyzed for income and evaluation of the income to cost (R/C) ratio in various planting patterns, both for red chilies and shallots by measuring 4 methods of planting patterns including non-IPM single cropping; IPM single cropping; non-IPM double cropping; and IPM double cropping. The results of the research show that the greatest value in measuring IPM double cropping is an increase in farming production, farming income, and total farming during the rainy season in the Tegal Regency location. This study also provides valuable insights for farmers and policy makers in encouraging sustainable horticultural farming practices and minimizing the impact of climate change in the region.